Improving Route Discovery for AODV to Prevent Blackhole and Grayhole Attacks in MANETs - ERRATA - Jhaveri, Rutvij H.; Patel, Sankita J. (INFOCOMP Journal of Computer Science, 2012)
This errata is published to clarify the differences between the paper and our previously pub- lished related work. This is a set of errata of the paper previously published in the March 2012 edition of the journal, clarifying the differences between the paper and other related work from the authors published in other conferences. The original paper is available at http://algol.dcc.ufla.br/ojs/index.php/INFOCOMP/article/view/346/330